Sex object a memoir - Valenti, Jessica 1978- (Dey St., 2016)
""Who would I be if I lived in a world that didn't hate women?" Hailed by the Washington Post as "one of the most visible and successful feminists of her generation," Jessica Valenti has been leading the national conversation on gender and politics for over a decade. Now, in a memoir that Publishers Weekly calls "bold and unflinching," Valenti explores the toll that sexism takes on women's lives, from the everyday to the existential. From subway gropings and imposter syndrome to sexual awakenings and motherhood, Sex Object reveals the painful, embarrassing, and sometimes illegal moments that shaped Valenti's adolescence and young adulthood in New York City. In the tradition of writers like Joan Didion and Mary Karr, Sex Object is a profoundly moving tour de force that is bound to shock those already familiar with Valenti's work, and enthrall those who are just finding it"...